Description of Female Students' Motivation for Achieving Class I Laboratory Practice Targets at Surya Mandiri Midwifery Academy, Bima City - Faturahmah, Erni; Lily Marfuatun (Jurnal EduHealth, 2022)
Motivation is something that underlies a person's every action. When someone feels that there is a need that must be met, then a desire arises to satisfy or fulfill that need. In clinical laboratory learning there are targets that must be achieved by students as a form of follow-up to theoretical and laboratory learning in class. The aim of this research is to describe the motivation for achieving targets for class II laboratory practice for students at the Surya Mandiri Midwifery Academy . This research is a quantitative descriptive research, with an approach case control . The population in this research is students level II with a total sample of 48 students , total sampling technique . Analysis used is analysis univariate  with using a questionnaire instrument And sheet checklist . Results study description motivation achievement of Class II Laboratory Practice target , High 46 ( 95.8 %), Fair 2 (4.2%), somewhat low 0 (0%), low 0 (0%), very low 0 (0%). Based on the research results, it is necessary Students maintain motivation in the next practicum so that targets can be achieved more optimally.